A pragmatic study of speech as an instrument of power: Analysis of the 2016 USA presidential debate - Misyi Gusthini; Cece Sobarna; Rosaria Mita Amalia (Studies in English Language and Education, 2018)
This research was aimed at analyzing the speeches of Donald Trump and of Hillary Clinton in the USA Presidential candidates’ debates as instruments of power. The data is a presidential final debate video of Trump and Clinton made in September 2016 which has been converted into a transcript. The data analyzing technique is divided into three steps: 1) describing the context, 2) analyzing the illocutionary acts, and 3) analyzing the power dimensions. The results of this research show that the speakers use the speech act as an instrument of power with classifications of representative, commissive and expressive. In this regard, the researchers found that the speakers demonstrated their power to try to convince the voters in their society to trust them to be the president. The research results also showed that the usage of speech in debate as an instrument of power can influence the voters especially on Election Day.